Lower nanometer-scale size limit for the deformation of a metallic glass by shear transformations revealed by quantitative AFM indentation - Caron, Arnaud; Bennewitz, Roland (Beilstein Journal of Nanotechnology, 2015)
We combine non-contact atomic force microscopy (AFM) imaging and AFM indentation in ultra-high vacuum to quantitatively and reproducibly determine the hardness and deformation mechanisms of Pt(111) and a Pt57.5Cu14.7Ni5.3P22.5 metallic glass with unprecedented spatial resolution. Our results on plastic deformation mechanisms of crystalline Pt(111) are consistent with the discrete mechanisms established for larger scales: Plasticity is mediated by dislocation gliding and no rate dependence is observed. For the metallic glass we have discovered that plastic deformation at the nanometer scale is not discrete but continuous and localized around the indenter, and does not exhibit rate dependence. This contrasts with the observation of serrated, rate-dependent flow of metallic glasses at larger scales. Our results reveal a lower size limit for metallic glasses below which shear transformation mechanisms are not activated by indentation. In the case of metallic glass, we conclude that the energy stored in the stressed volume during nanometer-scale indentation is insufficient to account for the interfacial energy of a shear band in the glassy matrix.
Keywords: AFM indentation; dislocation; metallic glasses; metals; plasticity; shear transformation